BookArmor: a sustainable solution for textbooks longevity and sustainability / Aemillyawaty Abas … [et al.] - Abas, Aemillyawaty; Nor Azlan, Adam Ahmad; Muhammad, Nur Syuhada; Muhammad Rahmat, Muhammad Luqmanul Hakim (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Abstract An innovative product named as BookArmor is designed to repurpose plastic sheets binding that commonly used for report covers, into reusable shields specifically tailored for softcover Malaysian textbooks. The primary aim of BookArmor is to mitigate the prevalent issue of textbook wear and tear within Malaysian schools, where textbooks are repeatedly used across multiple student batches. By transforming plastic waste into protective covers, BookArmor extends the lifespan of textbooks and contributes to sustainable practices in education. The product's development involves a simple little to no cost to ensure softcover textbooks a robust protection akin to traditional hardcover books. BookArmor's thick, durable property provides almost any size of school textbook, safeguarding them from damage caused by daily use and handling. Moreover, BookArmor aligns with global sustainability goals by promoting the reuse of plastic materials, reducing environmental impact, and fostering a culture of eco-consciousness among students and educators. The potential implications of BookArmor extend beyond its immediate protective function as it serves as a tangible example of innovative solutions to pressing environmental and educational challenges. As the world increasingly focuses on sustainability and resource optimization, BookArmor represents a promising step towards integrating eco-friendly practices into everyday educational activities.